Der Hamburger Professorinnen- und Professorenkatalog (HPK). Reden der Zentralen Veranstaltung der Universität Hamburg am 26. Januar 2017 anlässlich der Freischaltung des HPK - Nicolaysen, Rainer (Hamburger Universitätsreden Neue Folge, 2018)
This volume documents speeches of the University's central event on the occasion of the release of the Hamburg catalogue of professors, supplemented by an epilogue.